FAKTOR YANG MEMPENGARUHI MINAT ADOPSI E-COMMERCE DAN PENGARUHNYA PADA TINGKAT PENJUALAN UMKM DI SURAKARTA - nuramalina nuramalina (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
Today, the e-commerce use is increasingly popular. Especially with the Covid-19 pandemic, which make many consumers start using e-commerce. To deal with it, MSME needs to adopt e-commerce in order to be able to survive during Covid-19 pandemic. This study aims to analyze factors that influence the adoption of e-commerce using Unified Theory of Acceptance and Use of Technology (UTAUT) model and its effect on the level of sales of MSMEs. The sample in this study were 100 MSME in Surakarta. Data processing using SPSS. The results show that performance expectancy, effort expectancy, social influences, and facilitating conditions have an influence on e-commerce adoption, but partially only social influences have influence on e-commerce adoption. Furthermore, the adoption of e- commerce has an influence on the level of sale